An Analytical Study Of Post-Pandemic Fictions With A Focus On Iraq: Crisis, Recovery, And Social Transformation In Contemporary English Novels (Journal of the College of Basic Education, 2026)
The COVID-19 pandemic has reshaped societies across the globe, not only through its devastating impact on public health but also by destabilizing economies, social relations, and cultural production. Beyond the immediate crisis, it has generated new modes of storytelling, inspiring a growing body of literary works that grapple with themes of vulnerability, resilience, and transformation in the face of systemic disruption. Within this broader context of global post-pandemic imaginaries, Iraqi literature written in English provides a particularly compelling case.This paper investigates post-pandemic fiction in contemporary Iraqi writing, focusing on how narratives articulate crisis, recovery, and social transformation in a country already marked bydecades of war, sanctions, and occupation. Through close readings of works by Ahmed Saadawi, Sinan Antoon, and Hassan Blasim, the study examines how Iraqi authors engage with trauma, resilience, and the reconstruction of meaning under conditions of prolonged instability. The concept of post-pandemic fiction is redefined here to encompass not only responses to health crises such as COVID-19 but also the long-term disruptions of conflict, underscoring the parallels between global pandemics and Iraq’s systemic ruptures.Beyond the canonical male voices, the paper incorporates gendered perspectives by highlighting the contributions of Betool Khedairi, Inaam Kachachi, and Helen Benedict, whose narratives foreground women’s experiences of war, displacement, and resilience. It also analyzes the role of the diaspora, showing how writers based in the United States and Europe construct a transnational memory that mediates between Iraqi trauma and global audiences. Finally, the study adopts a comparative lens, situating Iraqi fiction alongside Syrian and Lebanese post-crisis literatures, revealing shared themes of exile, memory, and identity reconstruction.By integrating these dimensions, the article argues that Iraqi post-pandemic fiction functions as both an archive of collective trauma and an imaginative laboratory for resilience and social renewal. It highlights the capacity of literature to bridge local and global contexts, transforming the Iraqi experience into a universal reflection on crisis, adaptation, and the possibility of new futures.